A highly secure oblivious sparse coding-based watermarking system for ownership verification. Issue 4 (March 2015) - Tareef, Afaf; Al-Ani, Ahmed
Highlights A novel sparse coding-based watermarking system is proposed to tackle security issues. The watermark is encoded as a function of its carrier using host-based dictionary. Our system improves the imperceptibility and robustness of image watermarking. The high compression and the strong encryption are some of sparse coding advantages.